The Influence Of Training, Development, Motivation, And Competence On Employee Work Quality At The Ministry Of Religious Affairs Of South Bengkulu - Derli Suflan; Karona Cahya Susena; Dodi Hardinata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The aim of this study is to determine the effect of training, development, motivation, and competence on employee work quality at the Ministry of Religious Affairs of South Bengkulu. The data collection method used in this study was a questionnaire technique, with a sample of 40 employees from the Ministry of Religious Affairs of South Bengkulu. The results of the study show that the multiple linear regression equation is Y = -0.497 + 0.160X1 - 0.175X2 - 0.107X3 + 1.131X4 + 0.565. The variables of training (X1) and competence (X4) have a positive effect on improving employee work quality at the Ministry of Religious Affairs of South Bengkulu, meaning that the higher the training and competence, the higher the work quality. Meanwhile, development (X2) and motivation (X3) have negative coefficients, indicating that in this study both variables do not contribute positively to improving work quality. Overall, competence is the most dominant factor influencing work quality compared to the other variables. The training test (X1) shows tcount 2.836 > ttable 0.681 and a significance value of 0.008 < 0.05, so Ha is accepted and Ho is rejected, meaning training has a positive and significant effect on employee work quality. The development test (X2) shows tcount -3.195 < ttable 0.681 and significance 0.003 < 0.05, so Ha is accepted and Ho is rejected, meaning development has a positive and significant effect on employee work quality. The motivation test (X3) shows tcount -0.759 < ttable 0.681 and significance 0.453 > 0.05, so Ha is accepted and Ho is rejected, meaning motivation has no effect on employee work quality. The competence test (X4) shows tcount 7.709 < ttable 0.681 and significance 0.000 < 0.05, so Ha is accepted and Ho is rejected, meaning competence has a positive and significant effect on employee work quality. Based on the comparison between Fcount and Ftable, Fcount is greater than Ftable, namely 18.736 > 2.49. Therefore, the hypothesis is accepted, meaning there is a simultaneous effect of training (X1), development (X2), motivation (X3), and competence (X4) on employee work quality at the Ministry of Religious Affairs of South Bengkulu. This is also supported by a significance value of 0.000 < 0.05.